The complex understanding of Article 12 of the Convention on the Rights of Persons with Disabilities - Constantino Caycho, Renato Antonio (2022)
The adoption and implementation of the Convention on the Rights of Persons with Disabilities drastically changed the understanding of the rights of persons with disabilities. The right to legal capacity (or legal agency) of persons with disabilities stands out, among other issues needed for its implementation. The Convention recognizes that persons with disabilities can make decisions and their disability is not ground for denying legal capacity. This goes against what most Civil Codes state in our region. To guarantee said right, it is necessary that States recognize support for legal capacity that are guarded by safeguards. These will prevent abuse, undue influence and conflict of interest. This article presents the different debates that have occurred at the theoretical level regarding these new institutions. Article 12 forces us to rethink several legal terms such as the juridical act and its grounds for voidness and voidability; informed consent or unfitness to plead.